2021
DOI: 10.1002/jbm.b.34775
|View full text |Cite
|
Sign up to set email alerts
|

Low‐shrinkage‐stress nanocomposite: An insight into shrinkage stress, antibacterial, and ion release properties

Abstract: The aims are: (a) To develop the first low-shrinkage-stress nanocomposite with antibacterial and remineralization capabilities through the incorporation of dimethylaminododecyl methacrylate (DMAHDM) and nanoparticles of amorphous calcium phosphate (NACP); (b) to investigate the effects of the new composite on biofilm inhibition, mechanical properties, shrinkage stress, and calcium (Ca) and phosphate (P) ion releases. The low-shrinkage-stress resin consisted of urethane dimethacrylate and triethylene glycol div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Moreover, the polymerization stress of the new composite was 40% lower than that of traditional composite control [111]. Also, the new composite has a strong antibiofilm activity that decreased the S.mutuns colonies to the minimum levels [112,113]. Another study conducted by Filemban et al concluded that the novel resin composite reduced the stress without compromising other properties, Figure 4.…”
Section: Using Hydrolytically Stable Monomers With Antibacterial and ...mentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, the polymerization stress of the new composite was 40% lower than that of traditional composite control [111]. Also, the new composite has a strong antibiofilm activity that decreased the S.mutuns colonies to the minimum levels [112,113]. Another study conducted by Filemban et al concluded that the novel resin composite reduced the stress without compromising other properties, Figure 4.…”
Section: Using Hydrolytically Stable Monomers With Antibacterial and ...mentioning
confidence: 91%
“…The researchers developed a hydrolytically stable low-shrinkage-stress polymer containing UDMA and TEG-DVBE (U1V1). It was mixed with dimethylaminododecyl methacrylate monomer (DMAHDM)-with a carbon chain length of 16, which is a highly effective, contact-killing, long-lasting antibacterial material [110][111][112][113][114]. Moreover, adding bioactive nanoparticles of amorphous calcium phosphate (NACP) was advantageous to dental tissues to regenerate the lost minerals and buffer the acidic environment by releasing calcium and phosphate ions to the enamel and dentin under low pH conditions [110][111][112][113][114].…”
Section: Using Hydrolytically Stable Monomers With Antibacterial and ...mentioning
confidence: 99%
“…The low-shrinkage-stress (LSS) resin was formulated using 55.8% UDMA (Esstech, Essington, PA, USA) and 44.2% TEG-DVBE (mass %), following previous studies [30,34]. This resin was designated as "UV".…”
Section: Formation Of Composites Containing Different Mass Fractions ...mentioning
confidence: 99%
“…In this study, Heliomolar (Ivoclar, Ontario, Canada) was used as a commercial control. It is a bioactive material that has the ability to release fluoride, according to previous studies [23,34]. The objective of this study was to investigate the antimicrobial efficacy and mechanical properties of the new formulations.…”
Section: Formation Of Composites Containing Different Mass Fractions ...mentioning
confidence: 99%
See 1 more Smart Citation